Evaluation of air cargo connectivity and policy in Thailand - Tipavinee Suwanwong (2018)
© 2018 Elsevier Ltd This study evaluates the air cargo connectivity of Suvarnabhumi airport in Thailand by developing an air cargo connectivity model that includes new air cargo operation deficiency factors. Our model is developed and extended from the NetCargo model and assesses the impact of air cargo operation deficiency of airports/airlines on their air cargo performance. The analysis shows that short-shipped cargo is the result of air cargo operation deficiency and has a big impact on overall air cargo connectivity. The finding presents a big difference between the results from both models. This result shows significant differences in airport strategy and planning policy. The finding suggests that our proposed model is practically suitable for the Asian region. We also discuss policy recommendations, such as the improvement of e-AWB, to improve the ability of air cargo transport in Thailand to prepare and cope with future demand.